TEACHER'S EFFORTS IN HANDLING UNDERACHIEVER STUDENTS IN CLASS VII STUDENTS AT MTsN 1 KOTA KEDIRI - Mubarok, Tohir Al; Laili, Ummiy Fauziyah; Umatin, Choiru (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This research aims to address a teacher's efforts in dealing with students who experience underachievers in class VII at MTsN 1 Kota Kediri. In this study, the qualitative approach was included in the case study research. Techniques for collecting data include; interviews, observation, and documentation. In the data analysis section, there are several steps: data reduction, data presentation, and then a conclusion is drawn by checking the validity of the data carried out by participation and triangulation. The research findings are: The teacher's efforts in dealing with underachiever students in class VII students at MTsN 1 Kota Kediri by identifying problems with underachiever students, the teacher conducts, approaches and directs the underachiever students, the teacher provides the correct pattern of thinking for underachiever students, provides effective learning style in underachiever students, instils a disciplined attitude. Regarding the factors supporting underachiever students in class VII students at MTsN 1 Kota Kediri, namely support from the homeroom teacher for class VII underachiever children, other teachers fully support handling underachiever students, and teachers use school facilities and infrastructure as optimally as possible. The inhibiting factors in dealing with underachiever students in class VII students at MTsN 1 Kota Kediri are the lack of openness to underachiever students and problems in communication with parents.